The implementation of ecopedagogy in school education: A systematic literature review emphasizing elementary level contexts - Liesandra, Shalsabilla Octania (Journal of Critical Ecology, 2026)
Background: The increasing degradation of ecosystems and climate change underscores the importance of implementing ecopedagogy in elementary education to foster students’ ecological awareness. However, based on similar literature reviews, research on ecopedagogy at this educational level remains limited compared to studies conducted at the secondary school level. Methods: The method employed is an SLR using the PRISMA approach. Articles and journals were collected using tools such as Watase UAKE and Harzing’s Publish or Perish, which are integrated with the Scopus API to assist in retrieving indexed literature (Q1-Q4) from databases including ERIC, Elsevier, Emerald, MDPI, ScienceDirect, Springer, Taylor & Francis,and Wiley Online Library. The critical analysis drew exclusively on articles published in peer-reviewed journals. The researcher also ranked and selected the top 10 most-cited and relevant articles for further analysis. Findings: The effective implementation of ecopedagogy through appropriate strategies offers several advantages in enhancing elementary students’ environmental literacy and strengthening collaboration among teachers and school stakeholders by integrating local cultural values and technology, involving school organizations, applying storytelling-based approaches, and enhancing digital STEAM practices. These competencies are essential to equipping students with the skills they need to face future challenges. Conclusion: Environmental education in elementary schools can serve as a crucial foundation for developing sustainability competencies among Indonesia’s younger generation when designed through the integration of direct experiences and strong education policy. However, this sector continues to face several constraints, including conceptual and methodological gaps, geographical disparities, and limitations in human resource capacity. Novelty/Originality of this article: Based on previous relevant literature, there is still a limited number of studies that have applied the SLR method to examine ecopedagogy in elementary education, especially in Indonesia. Thus, this study employs an SLR approach to expand future methodological perspectives and to discuss the implementation of ecopedagogy within the global elementary education context.